PENGARUH BERBAGAI JENIS BAHAN PEMBENAH TANAH TERHADAP INFEKTIVITAS BAKTERI RHIZOBIUM YANG BERSIMBIOSIS DENGAN KEDELAI PADA GAMBUT - Nurhayati; Razali (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2013)
The peat soil is very potential to be developed, but in other side, the peat soil has some problems that so complex, namely the ugly physical characteristic, chemical and biological, in that case, to use as a farmland, some of its characteristic that influence on the plants need to be repaired. The purpose of this research to look at the influence of some soil repairer materials types to the infectivity of Bradyrhizobium. The research was conducted in the greenhouse of the USU Agriculture Faculty since March to November 2008. This research uses the non-factorial completely randomized design which consists of 13 treatments and two repeats. The treatments tested include, control (A0), dolomite lime (A1), sea mud (A2), lime + sea mud (A3), Bradyrhizobium (A4), mos (A5), Isolates mycorrhizal of peat soil (A6), isolates mycorrhizal of the mineral soil (A7), Bradyrhizobium+mos (A8), mos + Isolates mycorrhizal of peat soil (A9), mos+ isolates mycorrhizal of the mineral soil (A10), Bradyrhizobium+mos+ Isolates mycorrhizal of peat soil (A11), Bradyrhizobium+mos+ Isolates mycorrhizal of mineral soil (A12). The variable observed that is amount of root nodules / pot. The variable is analyzed non-factorial with the Excel program, the further testing of DMRTI. The research result for giving various types of soil repairer materials very significant effect on the amount of root nodules / pot. Key Words: Peat soil, soybean, Bradyrhizobium, infectivity